Internal Control as ‘Restraint’ or ‘Guidance’: A Husserlian Phenomenological Study of the Experiences of Administrative Employees at PT Galva Makassar - beloan, Bertha; Alimuddin, Alimuddin; Said, Darwis; Sani, Ahmad (Amkop Management Accounting Review (AMAR), 2025)
Internal Control (IC) is often seen as a helpful guideline for workflow, but in practice, administrative employees often view it as a restriction, leading to resistance and creative ways of following the rules. This qualitative study uses Husserlian Descriptive Phenomenology to explore how administrative employees at PT Galva Makassar experience the tension between seeing IC as a 'constraint' or a 'guideline' in their daily work. In-depth interviews with five participants showed that senior employees see PI, especially strict authorization and reconciliation, as 'guidelines for life' and a personal safety net. For them, PI helps avoid blame, builds professional pride, and encourages voluntary compliance. On the other hand, new employees or those with fast-paced targets, like Sales Staff, often feel that PI is too bureaucratic and signals a lack of trust from management. This can limit their initiative, lower efficiency, and hurt morale. Still, experienced employees also see these procedures as a way to ensure data accuracy and as a professional defense, finding positive value in the constraints. The study concludes that PI works best when employees internalize it, not just when the system is well-designed. Management should focus on communicating PI in a way that supports employees and acts as a professional guide, not just as a form of control.